Potts Shunt to Be Preferred Above Atrial Septostomy in Pediatric Pulmonary Arterial Hypertension Patients: A Modeling Study - Delhaas, Tammo; Koeken, Yvette; Latus, Heiner; Apitz, Christian; Schranz, Dietmar (Frontiers in Physiology, 2018)
Aims To quantitatively evaluate the basic pathophysiological process involved in the creation of Eisenmenger syndrome in pediatric pulmonary arterial hypertension (PAH) patients by either atrial septostomy (AS) or Potts shunt as well as to predict the effects of AS or Potts shunt in future PAH patients. Methods The multi-scale lumped parameter CircAdapt model of the cardiovascular system was used to investigate the effects of AS and Potts shunt on cardiovascular hemodynamics and mechanics, as well as on oxygen distribution in moderate to severe PAH. The reference simulation, with cardiac output set to 2.1 l/min and mean systemic pressure to 61 mmHg, was used to create a compensated moderate PAH simulation with mPAP 50 mmHg. Thereupon we created a range of decompensated PAH simulations in which mPAP was stepwise increased from 50 to 80 mmHg. Then we simulated for each level of mPAP the acute effects of either Potts shunt or AS with connection diameters ranging between 0 - 16 mm. Results For any mPAP level, the effect on shunt flow size is much larger for the Potts shunt than for AS. Whereas right ventricular pump work in Potts shunt is mainly dependent on mPAP, in AS it depends on both mPAP and the size of the defect. The effects on total cardiac pump work were similar for Potts shunt and AS. As expected, Potts shunt resulted in a drastic decrease of lower body oxygen saturation, whereas in AS both the upper and lower body oxygen saturation decreased, though not as drastically as in Potts shunt. Conclusions Our simulations support the opinion that a Potts shunt can transfer suprasystemic pulmonary arterial hypertension to an Eisenmenger physiology associated with a right-to-left shunt at the arterial level. Contrary to the current opinion that Potts shunt in PAH will decompress and unload the right ventricle, we show that while a Potts shunt does lead to a decrease in mPAP towards mean systemic arterial pressure, it does not unload the right ventricle because it mainly diverts flow from the pulmonary arterial system towards the lower body systemic arteries.